A comparative study on psychrophilic and mesophilic biooxidation of ferrous iron by pure cultures of Acidithiobacillus ferrooxidans and Acidithiobacillus ferrivorans - Seitkamal, K.N.; Zhappar, N.K.; Shaikhutdinov, V.M.; Shibaуeva A.K.; Sagyndykov, U.Z. (Fundamental and Experimental Biology, 2020)
Biological oxidation of ferrous sulfate by Acidithiobacillus ferrooxidansand Acidithiobacillus ferrivoransis an important process in the bioleaching of minerals and the treatment of acid mine drainage. The rate at which biooxidation reactions take place is directly related to the microorganisms’growth temperature. Decreasing the temperature of reaction causes both a decrease on the chemical reactions rates and a decrease on bacterial growth. In this study, the effects of pH and temperatures on oxidation of ferrous sulfate by a native At. ferrooxidans and At. ferrivorans strains were investigated. The biooxidation tests conducted in shake flasks at 28 °C and 8 °C and at initial pH 1.6 for 5 days. During the experiment, the mesophilic iron oxidizers were capable of growing on ferrous iron at concentrations of 4.5 g/L at low and optimum temperature. However, the rate of mesophilic biooxidation of ferrous ironwas higher than that observed in the psychrophilic biooxidation. In conclusion, during the experiment the At. ferrivorans strain 535 showed high activity in oxidizing at low temperature than other strains. It means even at very low temperatures, microorganisms play an important role in the oxidation and leaching of sulphide ores.